A Constructive Method and a Guided Hybrid GRASP for the Capacitated Multi-Source Weber Problem in the Presence of Fixed Cost. Issue 2 (June 2015) - Luis, Martino; Salhi, Said; Nagy, Gábor
This paper presents a new variant of the capacitated multi-source Weber problem that introduces fixed costs for opening facilities. Three types of fixed costs are considered and experimented upon. A guided constructive heuristic scheme based on the concept of restricted regions and a greedy randomized adaptive search procedure (GRASP) are proposed. The four known data sets in the literature, typically used for the uncapacitated multi-source Weber problem, are adapted by adding capacities and facility fixed costs and used as a platform to assess the performance of our proposed approaches. Computational results are provided and some research avenues highlighted.